The Practice of Translanguaging and Teachers’ Perception on Its Use for Teaching Young Learners at Singaraja Montessori School - I Dewa Sri Agung Oktaviyanti Puspita Dewi; Ni Wayan Surya Mahayanti; Luh Gd Rahayu Budiarta (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to investigate translanguaging practices and teachers’ perceptions of its use for teaching young learners in a bilingual environment. The study was conducted in upper-primary class at Singaraja Montessori School. Employing a qualitative case study, the data were collected through observation and interview to gather information on translanguaging phenomenon in the context of bilingual young learners, especially at Singaraja Montessori School. Thematic analysis was used to find themes from the data. The findings indicate that translanguaging practices are initiated by both teachers and students. Furthermore, teachers hold a positive view toward translanguaging, which can be seen through their emotional responses, beliefs, and actions.